New distortion theorems for Sakaguchi functions - Çağlar, Mert; POLATOĞLU, YAŞAR (ELEMENT, R AUSTRIJE 11, 10000 ZAGREB, CROATIA, 2007)
Let A be the class of functions f (z) of the form f (z) = z + Sigma(infinity)(k=2), a(k)z(k) that are analytic in the open unit disk D = {(z) epsilon C | |z| < 1} in 1959, K. Sakaguchi [9] has considered the subclass of A consisting of those f (z) which satisfy Re (zf,(z)/f(z)-f(-z)) > 0, where z E D. We call such a function a "Sakaguchi function", and denote the class of those functions by Ss. Various authors have studied this class ([6, 7, 9, 10]). We obtain new distortion theorems, Koebe domain, k-quasiconformatity, and the radius of convexity for the class S-s.
Keywords: Sakaguchi function; starlike function; Koebe domain; k-quasiconformality; Sakaguchi işlevi; starlike fonksiyonu; Koebe alanı; K-kvazi konformluk